Exploring Patterns of Behaviour in Violent Jihadist Terrorists An analysis of six significant terrorist conspiracies in the UK - Clutterbuck, Lindsay (RAND Corporation, 2011)
An examination of the groups/cells and their 38 core individuals involved in the six most serious violent Jihadist terrorist conspiracies and attacks in the UK between 2004 and 2007 to see if they exhibited any specific types of behaviour.